The Effect of the PBL Model on Learning Outcomes Viewed from Mathematical Communication Ability of Students - Ningrum, Intan Dwi Agustina; Swastika, Annisa; Cahyo, Adi Nur (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
Teachers as educators need to apply various learning models in order to optimize student learning outcomes. In addition, teachers need to concern to the mathematical communication skills possessed by students. The purpose of this research was to analyze the effect of Problem Based Learning (PBL) model on Mathematics Learning Outcomes in terms of students' mathematical communication skills. This research is a quantitative research using experimental methods and using a factorial experiment design. The sampling technique used is purposive sampling technique. The instruments used in this research were questions on the test of mathematical communication ability and test questions on learning outcomes in the form of descriptions. Statistical analysis used the Friedman two way ANOVA test. The results showed that there was an effect between learning models and mathematical communication skills on student learning outcomes. Students who receive PBL learning have an average learning outcome higher than students who receive conventional learning. In addition, students had high mathematical communication skills get the highest average learning outcomes compared.